2001
DOI: 10.1159/000049004
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Concentrations of Dopamine Inhibit the Proliferation and Cytotoxicity of Human CD4+ and CD8+ T Cells in vitro: A Receptor-Mediated Mechanism

Abstract: Objective: Dopamine, a catecholamine neurotransmitter, influences growth and proliferation of lymphocytes. Pharmacological doses of dopamine have been shown to modulate T cell functions significantly, but no information is available on the effect of physiological concentrations of circulating dopamine on CD4+ and CD8+ T cell functions. This information may be of importance since significantly elevated plasma dopamine levels were observed in humans during uncoping stress, and suppression of T cell functions dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 25 publications
3
90
2
4
Order By: Relevance
“…Previous studies showing that pharmacological stimulation of DRD3 modulates cytokine production by human T cells in vitro (13,14,25), together with the results presented above, prompted us to investigate whether DRD3 expression contributes to CD4 + T cell differentiation into effector phenotypes. Whereas Drd3 2/2 CD4 + T cells induced IL-17A expression similarly to their WT counterparts under Th17-skewing conditions, they showed a significantly lower frequency of IFN-g-producing cells when exposed to Th1-polarizing signals (Fig.…”
Section: Th1 But Not Th17 Differentiation Is Favored By Drd3 Expresmentioning
confidence: 97%
“…Previous studies showing that pharmacological stimulation of DRD3 modulates cytokine production by human T cells in vitro (13,14,25), together with the results presented above, prompted us to investigate whether DRD3 expression contributes to CD4 + T cell differentiation into effector phenotypes. Whereas Drd3 2/2 CD4 + T cells induced IL-17A expression similarly to their WT counterparts under Th17-skewing conditions, they showed a significantly lower frequency of IFN-g-producing cells when exposed to Th1-polarizing signals (Fig.…”
Section: Th1 But Not Th17 Differentiation Is Favored By Drd3 Expresmentioning
confidence: 97%
“…The same authors have shown that pharmacologic D3R stimulation in human T cells potentiate expression of surface activation markers (33). In contrast, Saha et al (23,24) have shown that DA, at concentrations that should selectively stimulate D3R, inhibits human T cell proliferation.…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 97%
“…Regarding expression of DA receptors (DARs) in immune cells, these receptors have been found not only in cells of the innate immune response such as dendritic cells (DCs), NK cells, macrophages/monocytes and granulocytes (19)(20)(21) but also in cells of the adaptive immune response such as B cells, CD8 + T cells, and CD4 + T cells (22)(23)(24)(25)(26)(27)(28)(29)(30). Despite being lesser studied than in human T cells, DARs expression has also been described in murine T cells (26,31).…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine also is an agonist of α-and β-adrenergic receptors, but exerts its effects mainly via specific dopaminergic receptors that can be found on a large number of cells including lymphocytes (83). In physiological concentrations, dopamine inhibits the proliferation and cytotoxicity of human CD4 + and CD8 + lymphocytes in vivo and in vitro via the dopamine receptors (52,(84)(85)(86), paralleling the adverse effects of epinephrine and norepinephrine. Lately, the gut has also been identified as an alternate source of catecholamines during sepsis in rodents, releasing norepinephrine into the portal vein and thereby altering the functional state of hepatocytes and Kupffer cells, unexpectedly contributing to hepatocellular dysfunction during sepsis (87)(88)(89)(90).…”
Section: Foolishly Unlocking Pandora's Box?mentioning
confidence: 99%